Imperialisme baru - Hidayat, Nuim; Satria, Ivan (Jakarta : Gema Insani, 2009)
Issues on the new imperialism, liberalism, and terrorism related with anti-Islam sign in Indonesia; collected articles
Keywords: Islam -- Indonesia; Islam -- Social aspects -- Indonesia; Islam and social problems -- Indonesia; Islam and politics -- Indonesia